Chemistry for matriculation semester 2 - Norbani Abdullah; Lok, W. F. (SAP Publications (M) Sdn Bhd, 2023)
Chemistry for matriculation semester 2 is an introductory books which provides an excellent way for students undertaking Chemistry under the Matriculation programmed to understand key concepts, principles, facts and theories.